Perbanyakan Tanaman Melalui Stek Batang Mini Tanaman Singkong (Manihot esculenta Crantz.) untuk Pemulia Tanaman dan Produsen Benih - Ardian Ardian (Politeknik Negeri Lampung., 2013)
Cassava plant breeders and seed producers need a method of plant propagation through a semi-conventional ways to be able to supply rapidly the needs of seed varieties before and after the release of government. The purpose of this study was to determine the effect of various concentrations of indole-3-butyric acid and a number of nodes of cuttings on the growth of new shoots and roots of cassava cuttings. Plant material used in the form of cassava stems, which comes from a plant of 10 months old. This experiment used a randomized complete treatment is the number of the nodes: 1, 2, and 3 nodes with indole-3-butyric acid: 0; 500; 1000, and 2000 ppm. Each treatment was repeated 10 times with the experimental unit consists of 2 cuttings. Treatment of cuttings 3 nodes increase speed germinate, sprout cuttings percentage, number of shoots, number of leaves, number of nodes of new shoot and number of roots. The treatment of indole-3-butyric acid 2000 ppm increased growth in the number of shoots, number of leaves, number of nodes and number of roots. Interaction cuttings 3 nodes by giving indole-3-butyric acid 2000 ppm increased growth in the number of shoots, number of leaves, number of nodes and number of roots. Keywords: cassava, mini cutting, indole-3-butyric acid.